Cryptic humour in "Did you have to put on the light, Lili? : a short story of Yusuf Idris - Dadoo, Yousuf (Journal for semitics, 2005)
In the following narrative, Yusuf ldris descriptionbes the pitiful state of an Egyptian religious leader and his congregation. The former figure is totally ensnared by a beautiful Anglo Egyptian prostitute to a point where she becomes the object of his prostration, thereby replacing God. Most of the congregation remains heedless of its surroundings. This work may also be interpreted as a political allegory wherein the author, through the use of cryptic humour and various narrative and poetic devices highlights compliance between religious authorities and the state as well as obsequiousness of local political rulers to western powers. The masses remain oblivious to all these realities.